Life at the borderline: Responses of Ganges river dolphins to dry‐season flow regulation of river and canal habitats by the Farakka barrage. Issue 2 (27th December 2021) - Samad, Imran; Kelkar, Nachiket; Krishnaswamy, Jagdish
Abstract: Modification of river flows by dams and barrages has fragmented riverine habitats and threatened the survival of Indian subcontinental river dolphins. In this study, habitat use by endangered Ganges river dolphins in response to dry‐season operations (December‐March) of the Farakka barrage on the Ganga River, located about 20 km upstream of the India–Bangladesh border, was assessed. Ten surveys were conducted in: (i) the Ganga River below the barrage, where rapid changes in water levels were expected owing to barrage operations; (ii) the Farakka feeder canal with stable water levels; and (iii) the Hooghly River downstream of the canal. Dolphin distribution, water depth, fishing boat count and temperature were recorded in all surveys and the data were analysed in a dynamic occupancy modelling framework. Temporal trends in river discharge, primary productivity and fish availability were also estimated to explain river dolphin responses. Occupancy and colonization by dolphins increased in all stretches by spring/March, correlated with rising water temperature and increased fishing intensity, which was related to upstream migration of hilsa fish. In the Ganga River, dolphin occupancy in deep river pools remained stable, but resulted in increased overlap with fisheries as river flow declined. The feeder canal, with stable flows, witnessed increased colonization by dolphins, but also greater risk of bycatch in fishing nets. The canal that appeared as a hydrological refuge thus became an 'ecological trap'. The findings highlight the need for integration of flow maintenance and fishery regulations in the monitoring and management of canals as effective refuges for riverine species. We advocate the inclusion of ecological flow criteria and fishery regulations to reduce dolphin bycatch mortality, in the context of establishing river dolphin conservation plans and transboundary water‐sharing guidelines. The revision of the India–Bangladesh water‐sharing treaty in 2026 could incorporate the above considerations.